Holocene glacier fluctuations in Patagonia are modulated by summer insolation intensity and paced by Southern Annular Mode-like variability - Reynhout, Scott A.; Sagredo, Esteban A.; Kaplan, Michael R.; Aravena Donaire, Juan Carlos; Martini, Mateo A.; Moreno, Patricio I.; Rojas, Maisa; Schwartz, Roseanne; Schaefer, Joerg M. (My University, 2019)
Alpine glaciers are sensitive indicators of changes in climate, and their ubiquity in mountainous regions make them valuable proxies for terrestrial climate reconstructions worldwide. However, the timing and extent of glacier change across the South American mid-latitudes through the Holocene are still poorly constrained relative to their counterparts in the Northern Hemisphere. Here we report a new Be-10 surface exposure-based chronology of moraines recording a series of progressively less-extensive glacier advances of Glaciar Torre (Argentina, 49.3 degrees S/73.0 degrees W) since the Last Glacial Maximum, with expansions culminating at 17,600 +/- 900, 13,500 +/- 500, 9700 +/- 400, 6900 +/- 200, 6100 +/- 300, 4500 +/- 200, and 530 +/- 60 yr BP. The declining magnitude of Holocene glacier expansions parallels a gradual rise in local summer insolation intensity during the Holocene, while individual advances occurred during inferred negative Southern Annular Mode (SAM)-like states at centennial to millennial timescales. These observations suggest that (i) summer insolation intensity modulated antiphased trends in glacier extent in the polar hemispheres during the Holocene, and that (ii) centennial-scale 'SAM-like' temperature and precipitation anomalies paced glacier fluctuations throughout Patagonia. Given the persistence of the inferred 'SAM-like' anomalies throughout the Holocene, the modern measured trend towards positive SAM index conditions could mark the onset of a fundamental shift in the climate of the Southern Hemisphere midlatitudes that warrants consideration in projections of future climate. (C) 2019 Published by Elsevier Ltd.
Keywords: holocene; glaciation; paleoclimatology; south america; cosmogenic isotopes; geomorphology; glacial; insolation; southern annular mode